Pengaruh Kompensasi dan Kompetensi Terhadap Kinerja Karyawan Di Masa Pandemi Covid-19 Pada PT. Adira Dinamika Multi Finance Tbk. Bangkalan - Rachmat Mauluddin; S. Anugrahini Irawati (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study aims to understand the problems regarding the level of consumer expectations of the atmosphere and prices as well as to measure consumer satisfaction with the atmosphere and prices at Kedai Srikandi Kwanyar. Thus, the atmosphere and price variables can be identified in accordance with the needs and expectations of consumers as well as variables that require improvement. The samples taken in this study were consumers who were visiting and had transacted and had enjoyed the offerings from Kedai Srikandi Kwanyar. The analysis method used is the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results obtained based on the CSI method indicate that the overall level of customer satisfaction at Kedai Srikandi is included in the